Anti-interference control cable
By adopting multi-layer shielding and protective structures in the anti-interference control cable and adding modified hyperbranched amide polymer to the flame retardant crosslinked polyethylene material, the problem of low tensile strength retention rate of the aging of flame retardant crosslinked polyethylene material is solved, and the effect of improving the anti-electromagnetic interference capability and extending the service life of the anti-interference control cable is achieved.
Patent Information
- Application Number
- CN202510012607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The flame-retardant crosslinked polyethylene materials of existing anti-interference control cables have a low aging tensile strength retention rate and need to be improved to enhance aging resistance and safety.
It adopts a multi-layer shielding structure and a multi-layer shielding structure, including an inner copper-plastic composite belt shielding layer, an aluminum wire braided shielding layer, an outer copper-plastic composite belt shielding layer, a mica belt winding cladding and sheathing layer, and is made of flame retardant crosslinked polyethylene material, and a modified hyperbranched amide polymer is added to the material to improve tensile strength and aging resistance.
Effectively isolate external electromagnetic interference, improve the anti-electromagnetic interference capability of anti-interference control cables, extend the service life, and improve the safety and reliability of the cables.
Smart Images

Figure CN119418993B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable technology, and more specifically, to an anti-interference control cable. Background Art
[0002] Anti-interference control cable is a common cable, which is widely used in industrial automation, power transmission, communication and other fields, especially in electromagnetic interference environment, such as substations, chemical plants and other places. The anti-interference control cable of the prior art generally includes multiple cable cores, the outer peripheral surface of the multiple cable cores is provided with a sheathing layer, the outer peripheral surface of the sheathing layer is provided with a shielding layer, and the outer peripheral surface of the shielding layer is provided with a sheathing layer. Common shielding layers include copper foil, aluminum foil, copper mesh, aluminum mesh, etc. These materials can effectively reflect and absorb electromagnetic waves and reduce the influence of external electromagnetic interference. Common sheath layers include flame-retardant cross-linked polyethylene materials, which have good chemical corrosion resistance, elasticity, etc., effectively reduce the damage of anti-interference control cables during installation and use, and play a good protective role. Flame-retardant cross-linked polyethylene materials generally use linear low-density polyethylene prepolymer as the matrix, on this basis, antioxidants and flame retardants are added to improve flame retardancy and aging resistance. However, the applicant found in actual research that although adding antioxidants alone to flame-retardant cross-linked polyethylene materials improves aging resistance, the aging tensile strength retention rate is generally around 90%, which is still slightly poor and needs to be further improved. Summary of the invention
[0003] On the basis of maintaining good anti-electromagnetic interference capability of the anti-interference control cable, in order to improve the aging tensile strength retention rate of the flame-retardant cross-linked polyethylene material, enhance aging resistance, and improve the safety and reliability of the anti-interference control cable, the present application provides an anti-interference control cable, which adopts the following technical solution:
[0004] An anti-interference control cable comprises a plurality of cable cores which conflict with each other, the outer circumferences of the plurality of cable cores are wrapped with a glass fiber tape wrapping layer, the gaps between the glass fiber tape wrapping layer and the plurality of cable cores are filled with glass fiber fillers, and the outer circumference of the glass fiber tape wrapping layer is sequentially provided with an inner copper-plastic composite tape shielding layer, an aluminum wire braided shielding layer, an outer copper-plastic composite tape shielding layer, a mica tape wrapping layer, and a sheath layer from the inside to the outside; the sheath layer is made of a flame-retardant cross-linked polyethylene material through extrusion processing;
[0005] The flame-retardant cross-linked polyethylene material is mainly made of the following raw materials in parts by weight: 70-90 parts of linear low-density polyethylene prepolymer, 10-30 parts of ethylene-vinyl acetate prepolymer, 5-15 parts of maleic anhydride grafted polyethylene, 1-3 parts of stearic acid, 4-6 parts of modified hyperbranched amide polymer, 2-4 parts of cross-linking agent, 1-3 parts of antioxidant, 1-3 parts of ultraviolet absorber, and 15-25 parts of flame retardant; the modified hyperbranched amide polymer is obtained by reacting butyl succinic anhydride, 3-(2-aminoethylamino)propylamine, 1,4-butanediamine, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 4-hydroxybutyl acrylate glycidyl ether.
[0006] The anti-interference control cable of the present application is provided with an inner copper-plastic composite tape shielding layer, an aluminum wire braided shielding layer, and an outer copper-plastic composite tape shielding layer on the outer circumference of the glass fiber tape sheath, and the three are used to form a multi-layer shielding structure, which can effectively isolate external electromagnetic interference, reduce signal attenuation and distortion, and enhance the ability to resist electromagnetic interference, thereby ensuring the anti-electromagnetic interference ability of the anti-interference control cable, and is conducive to maintaining stable signal transmission. A mica tape sheathing layer and a sheath layer are also provided on the outer circumference of the outer copper-plastic composite tape shielding layer, and the two are used to form a multi-layer protective structure, which can enhance the strength, stability, chemical corrosion resistance, and flame retardancy of the anti-interference control current, reduce the damage of the anti-interference control cable during installation and use, and extend its service life.
[0007] The sheath layer of the present application is made of flame-retardant cross-linked polyethylene material through extrusion. In the flame-retardant cross-linked polyethylene material, linear low-density polyethylene prepolymer and ethylene-vinyl acetate prepolymer are used as the matrix, and the sum of the two is 100 parts, and a modified hyperbranched amide polymer is added on this basis, and butyl succinic anhydride, 3-(2-aminoethylamino)propylamine, and 1,4-diamine are used to react to form a hyperbranched polyamide, and 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether are used for grafting reaction to obtain a modified hyperbranched amide polymer. The modified hyperbranched amide polymer contains a large number of active groups such as amide groups, amine groups, ester groups, fluorine groups, ether groups, and epoxy groups, and also contains a large number of branched structures. By utilizing modified hyperbranched amide polymers, the compatibility between raw materials is significantly increased, the cross-linking density is improved, the stability of the three-dimensional network structure is enhanced, the bonding strength is improved, the structural defects are improved, the tensile strength and aging resistance are improved, and the tensile strength of the flame-retardant cross-linked polyethylene material is greater than 36MPa, and the aging tensile strength retention rate is greater than 97%. It has the characteristics of high tensile strength, high aging tensile strength retention rate, and good aging resistance, which improves aging resistance and service life, makes the sheath layer exhibit better comprehensive performance, and improves the safety and reliability of the anti-interference control cable.
[0008] Optionally, the modified hyperbranched amide polymer is mainly prepared by the following method:
[0009] S1. Mix 1,4-dioxane, toluene and butyl succinic anhydride under constant stirring, add 3-(2-aminoethylamino)propylamine dropwise, and continue stirring for 1-3 hours after the addition is complete. Distill under reduced pressure and dry to obtain an intermediate.
[0010] S2, under constant stirring at a temperature of 85-95° C., mixing water and 1,4-butanediamine, adding the intermediate, stirring for 2-4 hours, distilling under reduced pressure, and drying to obtain a hyperbranched polyamide;
[0011] S3. While stirring continuously, mix ethanol and hyperbranched polyamide, and respectively add 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether, and after the addition is completed, continue stirring for 18-22 hours, distill under reduced pressure, and dry to obtain a modified hyperbranched amide polymer.
[0012] Optionally, the weight ratio of the 1,4-butanediamine, the intermediate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 4-hydroxybutyl acrylate glycidyl ether is (0.1-0.3):(4-13):(3-6):(2-5).
[0013] By adopting the above technical scheme, the anhydride group in butyl succinic anhydride and the secondary amine group in 3-(2-aminoethylamino)propylamine are first reacted in an organic system to obtain an intermediate, which contains two amino groups and one carboxyl group. Then, the amino group in 1,4-butanediamine and the carboxyl group in the intermediate are reacted in an aqueous system, and the intermediate is gradually grafted with 1,4-butanediamine as the core to increase the number of branches to obtain a hyperbranched polyamide, which contains multiple amide groups, multiple amine groups, and multiple branches. Then, the amino group in the hyperbranched polyamide and the carbon-carbon double bond in 1,1,1,3,3,3-hexafluoroisopropyl acrylate and the carbon-carbon double bond in 4-hydroxybutyl acrylate glycidyl ether are reacted in an organic system to achieve grafting and obtain a modified hyperbranched amide polymer. The preparation method of the present application carries out the reaction in steps and realizes grafting, introduces a large number of active groups, increases the number of branches, ensures the stability of the preparation of the modified hyperbranched amide polymer, improves the tensile strength and aging resistance of the flame-retardant cross-linked polyethylene material, enhances the comprehensive performance of the sheath layer, and improves the overall performance and service life of the anti-interference control cable.
[0014] Optionally, the weight ratio of butyl succinic anhydride to 3-(2-aminoethylamino)propylamine is (9-11):(6-9).
[0015] By adopting the above technical scheme, the weight ratio of butyl succinic anhydride and 3-(2-aminoethylamino)propylamine is optimized, the yield and purity of the intermediate are improved, and then the performance of the modified hyperbranched amide polymer is improved, and the tensile strength and aging resistance of the flame-retardant cross-linked polyethylene material are improved.
[0016] Optionally, in step S1, the weight ratio of butyl succinic anhydride, 1,4-dioxane and toluene is (9-11):(50-70):(30-50); in step S2, the weight ratio of 1,4-butanediamine and water is (0.1-0.3):(70-130); in step S3, the weight ratio of 1,1,1,3,3,3-hexafluoroisopropyl acrylate and ethanol is (3-6):(70-130).
[0017] Optionally, the dropping time of the 3-(2-aminoethylamino)propylamine is 40-60 min, the dropping time of the 1,1,1,3,3,3-hexafluoroisopropyl acrylate is 40-60 min, and the dropping time of the 4-hydroxybutyl acrylate glycidyl ether is 40-60 min.
[0018] By adopting the above technical scheme, the dropping time of 3-(2-aminoethylamino)propylamine is optimized so that it can fully contact and react with butyl succinic anhydride, thereby reducing side reactions. The dropping time of 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether is also optimized so that it can fully contact and react with the intermediate, thereby ensuring the stability and use effect of the preparation of the modified hyperbranched amide polymer.
[0019] Optionally, the cross-linking agent is one or more of tert-butyl peroxide 3,5,5-trimethylhexanoate, diisopropylbenzene peroxide, tert-butyl perbenzoate, and methyl ethyl ketone peroxide.
[0020] By adopting the above technical solution, the selection of cross-linking agent is optimized, the raw materials form a three-dimensional network structure, the cross-linking degree is improved, the mechanical strength and heat resistance stability are enhanced, and the flame-retardant cross-linked polyethylene material exhibits better comprehensive performance.
[0021] Optionally, the antioxidant is one or more of antioxidant B215, antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 1024.
[0022] By adopting the above technical solution, the selection of antioxidants is optimized, the antioxidant properties of the flame-retardant cross-linked polyethylene material are improved, the stability of the anti-interference control cable during long-term use is ensured, and the service life is extended.
[0023] Optionally, the antioxidants are two kinds of antioxidants, antioxidant B215 and antioxidant 1010, and the weight ratio of antioxidant B215 to antioxidant 1010 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant B215 to antioxidant 1010 is 2:1, and the weight ratio can also be set to 1:1, 1:2, 1:3, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Optionally, the ultraviolet absorber is one or more of ultraviolet absorber UV-1130, ultraviolet absorber UV-531, ultraviolet absorber UV-329, and ultraviolet absorber UV-0.
[0025] By adopting the above technical solution, the selection of ultraviolet absorbers is optimized, the ultraviolet resistance of flame-retardant cross-linked polyethylene materials is improved, the aging of anti-interference control cables caused by long-term exposure to ultraviolet rays is reduced, and the service life of anti-interference control cables is extended.
[0026] Optionally, the ultraviolet absorber is a UV absorber UV-531 and a UV absorber UV-329, and the weight ratio of the UV absorber UV-531 to the UV absorber UV-329 is (1-3):(1-3). In multiple embodiments, the weight ratio of the UV absorber UV-531 to the UV absorber UV-329 is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Optionally, the flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, ammonium tripolyphosphate, and triphenylphosphine oxide.
[0028] By adopting the above technical scheme, the selection of flame retardants is optimized, the flame retardancy of the flame-retardant cross-linked polyethylene material is enhanced, and the anti-interference control cable exhibits a good flame retardant effect, preventing the spread of flames, reducing the risk of fire, and improving the safety and reliability of the anti-interference control cable.
[0029] Optionally, the flame retardant is aluminum hydroxide, magnesium hydroxide, and ammonium tripolyphosphate, and the weight ratio of aluminum hydroxide, magnesium hydroxide, and ammonium polyphosphate is (1-3): (1-3): (1-3). In multiple embodiments, the weight ratio of aluminum hydroxide, magnesium hydroxide, and ammonium polyphosphate is 1:2:1, and the weight ratio can also be set to 1:1:1, 1:1:2, 1:1:3, 1:3:1, 1:3:2, 1:3:3, 3:1:1, 3:1:2, 3:1:3, 3:3:1, 3:3:2, 3:3:3 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Optionally, the flame retardant cross-linked polyethylene material is mainly prepared by the following method:
[0031] Linear low-density polyethylene prepolymer, ethylene-vinyl acetate prepolymer, maleic anhydride grafted polyethylene, stearic acid, modified hyperbranched amide polymer, crosslinking agent, antioxidant, ultraviolet absorber, silane coupling agent and flame retardant are mixed, and then extruded and granulated at a temperature of 160-180° C. to obtain a flame-retardant cross-linked polyethylene material.
[0032] By adopting the above technical solution, the preparation of flame retardant cross-linked polyethylene material is facilitated. In multiple embodiments, the extrusion temperature is 170°C, and the extrusion temperature can also be set to 160°C, 162°C, 165°C, 168°C, 172°C, 175°C, 178°C, 180°C as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] In summary, this application has at least the following beneficial effects:
[0034] 1. The anti-interference control cable of the present application utilizes the cooperation between the inner copper-plastic composite tape shielding layer, the aluminum wire braided shielding layer, and the outer copper-plastic composite tape shielding layer to form a multi-layer shielding structure, which can effectively isolate external electromagnetic interference, reduce signal attenuation and distortion, and enhance the ability to resist electromagnetic interference, which is conducive to maintaining stable signal transmission;
[0035] 2. The sheath layer of the present application is made of flame-retardant cross-linked polyethylene material through extrusion processing, and a modified hyperbranched amide polymer is added to the flame-retardant cross-linked polyethylene material, which contains a large number of active groups such as amide groups, amino groups, ester groups, fluorine groups, ether groups, epoxy groups, etc., and also contains a large number of branched structures. The interaction between the active groups and the raw materials is utilized to increase the cross-linking density, enhance the stability of the three-dimensional network structure, improve structural defects, and enhance the bonding strength, so that the tensile strength of the flame-retardant cross-linked polyethylene material is greater than 36MPa, and the aging tensile strength retention rate is greater than 97%. It has the characteristics of high tensile strength, high aging tensile strength retention rate, and good aging resistance, thereby extending the service life and improving the safety and reliability of the anti-interference control cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic cross-sectional view of the anti-interference control cable of Example 1 of the present application.
[0037] Explanation of the accompanying drawings: 1. Cable core; 2. Glass fiber tape wrapping layer; 3. Glass fiber filler; 4. Inner copper-plastic composite tape shielding layer; 5. Aluminum wire braided shielding layer; 6. Outer copper-plastic composite tape shielding layer; 7. Mica tape wrapping layer; 8. Sheath layer. DETAILED DESCRIPTION
[0038] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0039] Preparation Example
[0040] Table 1 Amount of each raw material used in flame retardant cross-linked polyethylene materials (unit: kg)
[0041]
[0042] Preparation Example 1
[0043] A flame retardant cross-linked polyethylene material, the raw materials and raw material ratios of which are shown in Table 1.
[0044] Among them, the density of linear low-density polyethylene prepolymer is 0.92g / cm 3, a melt index of 2.0 g / 10 min; the mass content of vinyl acetate in the ethylene-vinyl acetate prepolymer is 18%, and the melt index is 2.5 g / 10 min; the maleic anhydride grafted polyethylene is maleic anhydride grafted polyethylene PE-g-MAH, and is selected from Guangdong Chuanheng New Material Technology Co., Ltd.; the cross-linking agent is 3,5,5-trimethylhexanoic acid tert-butyl peroxide; the antioxidants are antioxidant B215 and antioxidant 1010, and the weight ratio of antioxidant B215 to antioxidant 1010 is 2:1; the ultraviolet absorbers are ultraviolet absorbers UV-531 and ultraviolet absorbers UV-329, and the weight ratio of ultraviolet absorbers UV-531 and ultraviolet absorbers UV-329 is 1:1; the flame retardants are aluminum hydroxide, magnesium hydroxide, and ammonium tripolyphosphate, and the weight ratio of aluminum hydroxide, magnesium hydroxide, and ammonium tripolyphosphate is 1:2:1.
[0045] Moreover, the modified hyperbranched amide polymer is mainly prepared by the following method:
[0046] S1. Add 40 kg of toluene to 60 kg of 1,4-dioxane at a stirring speed of 1000 r / min and stir for 1 min. Add 10 kg of butyl succinic anhydride and stir for 2 min. Add 7.5 kg of 3-(2-aminoethylamino)propylamine dropwise for 50 min. After the addition is complete, continue stirring for 2 h. Remove 1,4-dioxane and toluene by vacuum distillation and dry to obtain an intermediate.
[0047] S2. Add 0.2 kg of 1,4-butanediamine to 100 kg of water at a stirring speed of 300 r / min and a temperature of 90°C, and stir for 1 minute. Add 8.7 kg of the intermediate obtained in step S1, and stir for 3 hours. Remove water by vacuum distillation, and dry to obtain a hyperbranched polyamide.
[0048] S3, under stirring speed of 300r / min, add all the hyperbranched polyamide obtained in step S2 to 100kg of ethanol, and stir for 5min. 4kg of 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 3.6kg of 4-hydroxybutyl acrylate glycidyl ether are added dropwise respectively, and the dropping time of 1,1,1,3,3,3-hexafluoroisopropyl acrylate is 50min, and the dropping time of 4-hydroxybutyl acrylate glycidyl ether is 50min. After the dropping is completed, continue stirring for 20h. Ethanol is removed by vacuum distillation, and dried to obtain a modified hyperbranched amide polymer.
[0049] A method for preparing a flame retardant cross-linked polyethylene material mainly comprises the following steps:
[0050] Ethylene-vinyl acetate prepolymer, maleic anhydride grafted polyethylene, stearic acid, modified hyperbranched amide polymer, crosslinking agent, antioxidant, ultraviolet absorber, silane coupling agent, flame retardant were added to linear low-density polyethylene prepolymer, and stirred for 5 minutes. Then, a twin-screw extruder was used to extrude and granulate at a temperature of 170°C and a screw speed of 400r / min to obtain a flame-retardant cross-linked polyethylene material.
[0051] Preparation Example 2
[0052] A flame retardant cross-linked polyethylene material, which differs from Preparation Example 1 in that the raw material ratio of the flame retardant cross-linked polyethylene material is different, and the raw material ratio of the flame retardant cross-linked polyethylene material is shown in Table 1.
[0053] Preparation Example 3
[0054] A flame retardant cross-linked polyethylene material, which differs from Preparation Example 1 in that the raw material ratio of the flame retardant cross-linked polyethylene material is different, and the raw material ratio of the flame retardant cross-linked polyethylene material is shown in Table 1.
[0055] Preparation Example 4
[0056] A flame retardant cross-linked polyethylene material, which is different from Preparation Example 1 in that the source of the modified hyperbranched amide polymer in the raw materials of the flame retardant cross-linked polyethylene material is different.
[0057] Moreover, the modified hyperbranched amide polymer is mainly prepared by the following method:
[0058] S1. Add 50 kg of toluene to 50 kg of 1,4-dioxane at a stirring speed of 1000 r / min and stir for 1 min. Add 11 kg of butyl succinic anhydride and stir for 2 min. Add 9 kg of 3-(2-aminoethylamino)propylamine dropwise for 60 min. After the addition is complete, continue stirring for 3 h. Remove 1,4-dioxane and toluene by vacuum distillation and dry to obtain an intermediate.
[0059] S2. Add 0.1 kg of 1,4-butanediamine to 70 kg of water at a stirring speed of 300 r / min and a temperature of 90°C, and stir for 1 min. Add 13 kg of the intermediate obtained in step S1, and stir for 4 h. Distill under reduced pressure to remove water, dry, and obtain a hyperbranched polyamide.
[0060] S3, under stirring speed of 300r / min, add all the hyperbranched polyamides obtained in step S2 to 70kg of ethanol, and stir for 5min. 6kg of 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 2kg of 4-hydroxybutyl acrylate glycidyl ether are added dropwise respectively, and the dropping time of 1,1,1,3,3,3-hexafluoroisopropyl acrylate is 60min, and the dropping time of 4-hydroxybutyl acrylate glycidyl ether is 60min. After the dropping is completed, continue stirring for 18h. Ethanol is removed by vacuum distillation, and dried to obtain a modified hyperbranched amide polymer.
[0061] Preparation Example 5
[0062] A flame retardant cross-linked polyethylene material, which is different from Preparation Example 1 in that the source of the modified hyperbranched amide polymer in the raw materials of the flame retardant cross-linked polyethylene material is different.
[0063] Moreover, the modified hyperbranched amide polymer is mainly prepared by the following method:
[0064] S1. Add 30 kg of toluene to 70 kg of 1,4-dioxane at a stirring speed of 1000 r / min and stir for 1 min. Add 9 kg of butyl succinic anhydride and stir for 2 min. Add 6 kg of 3-(2-aminoethylamino)propylamine dropwise for 40 min. After the addition is complete, continue stirring for 1 h. Remove 1,4-dioxane and toluene by vacuum distillation and dry to obtain an intermediate.
[0065] S2. Add 0.3 kg of 1,4-butanediamine to 130 kg of water at a stirring speed of 300 r / min and a temperature of 90°C, and stir for 1 minute. Add 4 kg of the intermediate obtained in step S1, and stir for 2 hours. Remove water by vacuum distillation, and dry to obtain a hyperbranched polyamide.
[0066] S3, under stirring speed of 300r / min, add all the hyperbranched polyamides obtained in step S2 to 130kg of ethanol, and stir for 5min. 3kg of 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 5kg of 4-hydroxybutyl acrylate glycidyl ether were added dropwise respectively, and the dropping time of 1,1,1,3,3,3-hexafluoroisopropyl acrylate was 40min, and the dropping time of 4-hydroxybutyl acrylate glycidyl ether was 40min. After the dropping was completed, the stirring was continued for 22h. Ethanol was removed by vacuum distillation, and the mixture was dried to obtain a modified hyperbranched amide polymer.
[0067] Comparative Preparation Example
[0068] Comparative Preparation Example 1
[0069] A flame retardant cross-linked polyethylene material, which is different from Preparation Example 1 in that no modified hyperbranched amide polymer is added to the raw materials of the flame retardant cross-linked polyethylene material.
[0070] Comparative Preparation Example 2
[0071] A flame retardant cross-linked polyethylene material, which differs from Preparation Example 1 in that an equal amount of a hyperbranched amide polymer is used to replace a modified hyperbranched amide polymer in the raw material of the flame retardant cross-linked polyethylene material.
[0072] Moreover, the hyperbranched amide polymer is mainly prepared by the following method:
[0073] S1. Add 40 kg of toluene to 60 kg of 1,4-dioxane at a stirring speed of 1000 r / min and stir for 1 min. Add 10 kg of butyl succinic anhydride and stir for 2 min. Add 7.5 kg of 3-(2-aminoethylamino)propylamine dropwise for 50 min. After the addition is complete, continue stirring for 2 h. Remove 1,4-dioxane and toluene by vacuum distillation and dry to obtain an intermediate.
[0074] S2. Add 0.2 kg of 1,4-butanediamine to 100 kg of water at a stirring speed of 300 r / min and a temperature of 90° C. and stir for 1 min. Add 8.7 kg of the intermediate obtained in step S1 and stir for 3 h. Distill under reduced pressure to remove water, dry, and obtain a hyperbranched amide polymer.
[0075] Comparative Preparation Example 3
[0076] A flame retardant cross-linked polyethylene material, which differs from Preparation Example 1 in that, in the raw materials of the flame retardant cross-linked polyethylene material, in the preparation method of the modified hyperbranched amide polymer, an equal amount of 1,1,1,3,3,3-hexafluoroisopropyl acrylate is used to replace 4-hydroxybutyl acrylate glycidyl ether.
[0077] Comparative Preparation Example 4
[0078] A flame retardant cross-linked polyethylene material, which differs from Preparation Example 1 in that, in the raw materials of the flame retardant cross-linked polyethylene material, in the preparation method of the modified hyperbranched amide polymer, an equal amount of 4-hydroxybutyl acrylate glycidyl ether is used to replace 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
[0079] Example
[0080] Example 1
[0081] An anti-interference control cable, refer to Figure 1The anti-interference control cable includes seven cable cores 1, and the cross-section of the cable core 1 is circular. One of the cable cores 1 is located in the center and forms a central cable core, and the remaining six cable cores 1 surround the outer circumference of the central cable core and form an outer cable core. The outer circumference of the six outer cable cores is wrapped with a glass fiber tape wrapping layer 2, and the glass fiber tape wrapping layer 2 is made of double wrapping of glass fiber tape, and the overlap rate of each wrapping layer is 20%. The gaps between the outer cable core and the central cable core, the glass fiber tape wrapping layer 2 and the six outer cable cores are filled with glass fiber fillers 3, and the glass fiber fillers 3 are glass fiber ropes. The seven cable cores 1 and the glass fiber fillers 3 are cabled simultaneously, and during the cabling process, the outer circumference of the six outer cable cores is double wrapped with glass fiber tape to form a glass fiber tape wrapping 2.
[0082] The outer peripheral surface of the glass fiber tape wrapping layer 2 is provided with an inner copper-plastic composite tape shielding layer 4, an aluminum wire braided shielding layer 5, an outer copper-plastic composite tape shielding layer 6, a mica tape wrapping layer 7, and a sheath layer 8 in sequence from the inside to the outside. The inner copper-plastic composite tape shielding layer 4 is formed by wrapping a polyester copper-plastic composite tape, and the wrapping overlap rate is 50%. The aluminum wire braided shielding layer 5 is formed by braiding an aluminum wire, and the braiding density is 80%. The outer copper-plastic composite tape shielding layer 6 is formed by wrapping a polyester copper-plastic composite tape, and the wrapping overlap rate is 50%. The mica tape wrapping layer 7 is formed by double wrapping of mica tape, and the wrapping overlap rate of each layer is 40%. The sheath layer 8 is formed by extrusion processing of a flame-retardant cross-linked polyethylene material, and the flame-retardant cross-linked polyethylene material is prepared by the method of Preparation Example 1.
[0083] Embodiment 2-5
[0084] An anti-interference control cable is disclosed, which differs from Example 1 in that the flame-retardant cross-linked polyethylene material used in the sheath layer has different sources, and the flame-retardant cross-linked polyethylene materials of Examples 2-5 are prepared by the methods of Preparation Examples 2-5 respectively.
[0085] Comparative Example
[0086] Comparative Examples 1-4
[0087] An anti-interference control cable is disclosed, which differs from Example 1 in that the flame-retardant cross-linked polyethylene material used in the sheath layer has different sources, and the flame-retardant cross-linked polyethylene materials of Comparative Examples 1-4 are prepared respectively by the methods of Comparative Preparation Examples 1-4.
[0088] Performance Testing
[0089] (1) The flame-retardant cross-linked polyethylene materials obtained in Preparation Examples 1-5 and Comparative Preparation Examples 1-4 were respectively taken, and the following performance tests were performed on the flame-retardant cross-linked polyethylene materials. The test results are shown in Table 2.
[0090] Among them, the tensile strength of flame retardant cross-linked polyethylene materials was tested in accordance with GB / T1040.1-2008 "Determination of tensile properties of plastics Part 1: General principles".
[0091] According to GB / T2951.1-1997 "General test methods for cable insulation and sheath materials Part 1: General test methods Section 2: Thermal aging test method", the flame retardant cross-linked polyethylene material was aged and the aging tensile strength retention rate was calculated.
[0092] Aging tensile strength retention rate / (%)=tensile strength of flame-retardant cross-linked polyethylene material after aging / tensile strength of flame-retardant cross-linked polyethylene material before aging×100%.
[0093] (2) The anti-interference control cables obtained in Examples 1-5 and Comparative Examples 1-4 were respectively taken, and the following performance tests were performed on the anti-interference control cables. The test results are shown in Table 2.
[0094] Among them, according to GB / T2408-2008 "Plastic combustion performance test method horizontal method and vertical method", the vertical combustion level of the anti-interference control cable is tested.
[0095] Table 2 Test results
[0096]
[0097] As can be seen from Table 2, the flame-retardant cross-linked polyethylene material of the present application has higher tensile strength, aging tensile strength and aging tensile strength retention rate, with a tensile strength of 36.52-38.56MPa, an aging tensile strength of 35.61-38.24MPa, and an aging tensile strength retention rate of 97.51-99.17%, and has the characteristics of high tensile strength, high aging tensile strength retention rate, and good aging resistance. In addition, the anti-interference control cable of the present application has a good vertical combustion level, a vertical combustion level of V-0, and has the characteristics of good flame retardancy, showing excellent comprehensive performance, and meeting market demand.
[0098] Comparative Preparation Examples 1-2 are compared, and Comparative Preparation Example 1 is used as the basis. Compared with Comparative Preparation Example 1, in Comparative Preparation Example 2, a hyperbranched amide polymer is added to the raw material of the flame retardant cross-linked polyethylene material. It can be seen that adding a hyperbranched amide polymer to the flame retardant cross-linked polyethylene material is beneficial to improving tensile strength and aging resistance. Combined with Preparation Example 1, compared with Comparative Preparation Example 1, in Preparation Example 1, a modified hyperbranched amide polymer is added to the raw material of the flame retardant cross-linked polyethylene material. It can be seen that on the basis of adding a hyperbranched amide polymer to the raw material of the flame retardant cross-linked polyethylene material, further modifying the hyperbranched amide polymer can effectively improve the interaction between it and the raw material, which is beneficial to improving the structural stability of the flame retardant cross-linked polyethylene material, and making the flame retardant cross-linked polyethylene material show better comprehensive performance.
[0099] Comparative Preparation Examples 2-4 and Preparation Example 1 are compared, and Comparative Preparation Example 2 is used as the basis. Compared with Comparative Preparation Example 2, Comparative Preparation Example 3 uses 1,1,1,3,3,3-hexafluoroisopropyl acrylate to treat the hyperbranched amide polymer; Comparative Preparation Example 4 uses 4-hydroxybutyl acrylate glycidyl ether to treat the hyperbranched amide polymer compared to Comparative Preparation Example 2; Preparation Example 1 uses 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether to treat the hyperbranched amide polymer compared to Comparative Preparation Example 2. It can be seen that grafting 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether on the surface of the hyperbranched amide polymer, introducing active groups such as ester groups, fluorine groups, ether groups, and epoxy groups can greatly improve the interaction between it and the raw materials, increase the crosslinking density, enhance the stability of the three-dimensional network structure, reduce structural defects, and further improve the tensile strength and aging tensile strength retention rate.
[0100] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. Anti-interference control cable, characterized by: The cable core (1) comprises a plurality of mutually conflicting cable cores, the outer circumferences of the plurality of cable cores (1) are wrapped with a glass fiber tape wrapping layer (2), the gaps between the glass fiber tape wrapping layer (2) and the plurality of cable cores (1) are filled with a glass fiber filler (3), and the outer circumference of the glass fiber tape wrapping layer (2) is provided with an inner copper-plastic composite tape shielding layer (4), an aluminum wire braided shielding layer (5), an outer copper-plastic composite tape shielding layer (6), a mica tape wrapping layer (7), and a sheath layer (8) in sequence from the inside to the outside; the sheath layer (8) is made of a flame-retardant cross-linked polyethylene material through extrusion processing; the flame-retardant cross-linked polyethylene material is made of the following raw materials in parts by weight: The invention comprises: 70-90 parts of linear low-density polyethylene prepolymer, 10-30 parts of ethylene-vinyl acetate prepolymer, 5-15 parts of maleic anhydride grafted polyethylene, 1-3 parts of stearic acid, 4-6 parts of modified hyperbranched amide polymer, 2-4 parts of crosslinking agent, 1-3 parts of antioxidant, 1-3 parts of ultraviolet absorber and 15-25 parts of flame retardant; the modified hyperbranched amide polymer is obtained by reacting butyl succinic anhydride, 3-(2-aminoethylamino)propylamine, 1,4-butanediamine, 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether; The modified hyperbranched amide polymer is prepared by the following method: S1. Mix 1,4-dioxane, toluene and butyl succinic anhydride under constant stirring, add 3-(2-aminoethylamino)propylamine dropwise, and continue stirring for 1-3 hours after the addition is complete. Distill under reduced pressure and dry to obtain an intermediate. S2, under constant stirring at a temperature of 85-95° C., mixing water and 1,4-butanediamine, adding the intermediate, stirring for 2-4 hours, distilling under reduced pressure, and drying to obtain a hyperbranched polyamide; S3, under constant stirring, ethanol and hyperbranched polyamide are mixed, 1,1,1,3,3,3-hexafluoroisopropyl acrylate and 4-hydroxybutyl acrylate glycidyl ether are added dropwise, and after the addition is completed, stirring is continued for 18-22 hours, and vacuum distillation is performed, and drying is performed to obtain a modified hyperbranched amide polymer; The weight ratio of the 1,4-butanediamine, the intermediate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 4-hydroxybutyl acrylate glycidyl ether is (0.1-0.3):(4-13):(3-6):(2-5); the weight ratio of the butyl succinic anhydride and 3-(2-aminoethylamino)propylamine is (9-11):(6-9).
2. The anti-interference control cable according to claim 1, characterized in that: The dropping time of the 3-(2-aminoethylamino)propylamine is 40-60 min, the dropping time of the 1,1,1,3,3,3-hexafluoroisopropyl acrylate is 40-60 min, and the dropping time of the 4-hydroxybutyl acrylate glycidyl ether is 40-60 min.
3. The anti-interference control cable according to claim 1, characterized in that: The cross-linking agent is one or more of tert-butyl peroxide 3,5,5-trimethylhexanoate, diisopropylbenzene peroxide, tert-butyl perbenzoate, and methyl ethyl ketone peroxide.
4. The anti-interference control cable according to claim 1, characterized in that: The antioxidant is one or more of antioxidant B215, antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 1024.
5. The anti-interference control cable according to claim 1, characterized in that: The ultraviolet absorber is one or more of the ultraviolet absorber UV-1130, the ultraviolet absorber UV-531, the ultraviolet absorber UV-329 and the ultraviolet absorber UV-0.
6. The anti-interference control cable according to claim 1, characterized in that: The flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, ammonium tripolyphosphate and triphenylphosphine oxide.
7. The anti-interference control cable according to claim 1, characterized in that: The flame retardant cross-linked polyethylene material is prepared by the following method: Linear low-density polyethylene prepolymer, ethylene-vinyl acetate prepolymer, maleic anhydride grafted polyethylene, stearic acid, modified hyperbranched amide polymer, crosslinking agent, antioxidant, ultraviolet absorber, silane coupling agent, and flame retardant are mixed, and then extruded and granulated at a temperature of 160-180° C. to obtain a flame-retardant cross-linked polyethylene material.
Citation Information
Patent Citations
High-temperature-resistant anti-corrosion insulating aerial cable and preparation method thereof
CN118496580A
Polyacrylonitrile-based modified material as well as preparation method and application thereof
CN118930750A